Gambaran BOR di Rumah Sakit Santa Elisabeth Medan - Pomarida Simbolon; Ruth Ema Liasta Tarigan (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
The importance of the Bed Occupancy Rate (BOR) indicator lies in its role as a parameter for efficiency and quality of service, as an indicator of the level of utilization and efficiency of the hospital, as a tool for evaluation and management planning, and as an ideal range to ensure optimal service. BOR is the percentage of bed usage over a certain period of time. It can be used for planning the construction and development of a hospital. One of the health service indicators that can be used to determine the quality level, utilization of facilities, and efficiency of health services. According to the Indonesian Ministry of Health, BOR is the percentage of bed occupancy over a certain period with an ideal value between 60-85% . This study uses a quantitative descriptive method aimed at systematically, factually, and accurately describing the inpatient service conditions at Santa Elisabeth Hospital Medan based on the Bed Occupancy Rate (BOR) indicator. Based on the community service activities, out of 12 rooms, 5 rooms have an ideal BOR value, and 7 rooms have a non-ideal BOR, with a total BOR value of 59.02%. Facilities, infrastructure, competent and adequate human resources, and management greatly influence the BOR value in the quality of hospital services. Non-ideal BOR values occur due to imbalances in these factors, thus they should be closely monitored to ensure the best health services.